Tinjauan Mashlahah Mursalah Terhadap Praktik Penetapan Harga Jual Beli di Rumah Makan dengan Sistem Prasmanan Tanpa Label Harga - Ali Mahfud; Umar Taufiq Mahri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the practice of price determination in the buffet system without price labels at Café Santiniketan, Pondok Modern Darussalam Gontor, Campus 4 Banyuwangi, from the perspective of mashlahah mursalah and Islamic economic principles. The research employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, Focus Group Discussions (FGD), and documentation. The data were analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The results indicate that Café Santiniketan has implemented the principles of fairness, honesty, and transparency in its transaction system. Payments are made before consumption to avoid elements of uncertainty (gharar), while pricing is based on the types of food selected and mutual consent (al-ridha). The buffet system provides flexibility for consumers to choose menu portions according to their needs. This practice aligns with the concept of mashlahah mursalah because it provides benefits for public interest and supports the economic independence of the pesantren community. However, challenges arise regarding the inconsistency between price and portion size, which has led to criticism from some customers. This condition highlights the need to improve price clarity to ensure compliance with the principle of fairness in Islamic economics. Overall, the implementation of the buying and selling system at Café Santiniketan has demonstrated good sharia-based economic practices, yet requires ongoing evaluation and development to ensure trust and customer satisfaction.